Muscle proximate composition of various food fish species and their nutritional significance: A review - Ahmed, Imtiaz; Jan, Kousar; Fatma, Shabihul; Dawood, Mahmoud A. O. (Journal of animal physiology and animal nutrition, 2022)
Today, there is a growing awareness about the importance of eating nutritious foods and fish is gaining momentum as a result of its unique nutritional benefits. Fish are considered as nutritionally valuable part of the human diet because of the presence of both macronutrients (proteins, lipids and ash) and micronutrients (vitamins and minerals). These nutrients are indispensable in human nutrition and have proven to be involved in several metabolic functions. The nutritional content can be used to rank different fish species based on their nutritional and functional benefits, allowing consumers to make better decisions according to their requirements. Proximate composition of fish includes determination of moisture, protein, fat and ash contents, which constitutes about 96%−98% of the total constituents of the fish body. The study of these components gives us a clear understanding in assessing the energy value of the fishes. In the present study, an attempt has been made to provide a concise review about the proximate composition of various fish species from different parts of the world in order to evaluate the high‐protein, low‐fat food with excellent nutritional values and to enlighten the different exogenous and endogenous factors that are actually responsible for their variation. The review also provides an insight into the characteristics of the chemical composition of various fish species, which are gaining importance for the sector involving fish and fishery products for domestic and foreign trade and for appreciating as animal feed all over the world.